Do people's world views matter? The why and how. [article]. - Chen, Sylvia Xiaohua
Over the past decades, personality and social psychologists have extensively investigated the role of self-views in individual functioning. Research on world views, however, has been less well studied due to overly specific conceptualizations, and little research about how and why they impact life outcomes. To answer why and how world views matter, we conducted 7 studies to examine the functions, antecedents, and consequences of generalized beliefs about the world, operationalized as social axioms (Leung et al., 2002). This research focused on 2 axiom factors, namely, social cynicism and reward for application. These axioms were found to explain individual differences in self-views over and above personality traits in Hong Kong and U.S. samples (Study 1) and to explain cultural differences in self-views in addition to self-construals among Mainland Chinese, Hong Kong Chinese, East Asian Canadians, and European Canadians (Study 2). Endorsement of social axioms by participants, their parents, and close friends was collected from Mainland China, Hong Kong, and Canada to infer parental and peer influences on world views (Study 3). World views affected psychological well-being through the mediation of positive self-views across 3 age groups, including children, adolescents, and young adults (Study 4) and over time (Study 5). The mediation of negative self-views was through comparative self-criticism rather than internalized self-criticism (Study 6). Holistic thinking moderated the effect of social cynicism on self-views and psychological well-being (Study 7). These results converge to show that world views as a distal force and self-views as a proximal force matter in people's subjective evaluation of their lives.-- (from the authors)
Keywords: Lam, Ben C. P; World views; Self-views.; Social axioms; Psychological well-being.; Holistic thinking